Linguacultural features of proverbs in German and Uzbek languages - Ibragimova Sojida Panjievna (Zien Journals, 2022)
In this article, the word proverb has its lexical meaning, as well as Uzbek folklore, their use among the people, and the peculiarities of German folklore, linguistic and cultural relations. The linguacultural features of each language are illuminated by control over several common human features in them
Keywords: proverb; German folklore; linguacultural; Uzbek folklore